100% renewable energy with pumped-hydro-energy storage in Nepal. Issue 2 (13th May 2021) - Lohani, Sunil Prasad; Blakers, Andrew
Abstract: A radical transformation of the global energy system is underway. Solar photovoltaics and wind now comprise three-quarters of the global net new electricity-generation-capacity additions because they are cheap. The deep renewable electrification of energy services including transport, heating and industry will allow solar and wind to largely eliminate fossil fuels over the next few decades. This paper demonstrates that Nepal will be able to achieve energy self-sufficiency during the twenty-first century. Nepal has good solar and moderate hydroelectric potential but has negligible wind- and fossil-energy resources. The solar potential is about 100 times larger than that required to support a 100% solar-energy system in which all Nepalese citizens enjoy a similar per-person energy consumption to developed countries, without the use of fossil fuels and without the environmental degradation resulting from damming Nepal's Himalayan rivers. Nepal has vast low-cost off-river pumped hydro-energy-storage potential, thus eliminating the need for on-river hydro storage and moderating the need for large-scale batteries. Solar, with support from hydro and battery storage, is likely to be the primary route for renewable electrification and rapid growth of the Nepalese energy system. Abstract : Developing countries such as Nepal could bypass the fossil-fuel era and transition directly to zero-emission renewables. Solar, with support from hydro and battery storage, is likely to be the primary route for renewable electrification and rapid growth of the Nepalese energy system. Graphical Abstract: